Query 06

#$&*

course MTH 279

12:35 pm 2/28

Query 06 Differential Equations*********************************************

Question:  3.3.4.  Solve the equation (6 t + y^3 ) y ' + 3 t^2 y = 0, with y(2) = 1.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution: 

This eq is not exact, and not separable, since:

M = 3t^2 y

N =6t + 3y

M_y = 3t^2

N_t = 6

M_y≠ N_t

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution: 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

 Self-critique rating:

*********************************************

Question:  3.3.6.  Solve the equation y ' = - ( y cos(t y) + 1) / (t cos(t y) + 2 y e^y^2) with y(0) = pi.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:  

 In form of Exact:

(t cos ty + 2y e^y^2) y' + (y cos ty + 1) = 0

M_y = cos ty - y^2 sin ty

N_t = cos ty - t^2 sin ty

Again these are not equal so the eq is not exact or separable.

@& We test the equation to see if it is exact, i.e., of the form

M dy + N dt = 0

with M_t = N_x.

The equation can be rearranged to

(t cos(t y) + 2 y e^(y^2)) dy + (y cos(t y) + 1) dt = 0

so it is of the form M dy + N dt = 0 with

M = t cos(t y) + 2y e^(y^2)

and

N = y cos(t y) + 1

M_t = cos(t y) - y t sin(t y)

and

N_y = cos(t y) - y t sin(t y)

These are equal, so our equation is of the form

dF = 0

with

F_y = t cos(t y) + 2y e^(y^2)

and

F_t = y cos(t y) + 1.

F_y = t cos(t y) + 2y e^(y^2) implies that

F = integral( (t cos(t y) + 2 y e^(y^2) ) dy = -sin(t y) + e^(y^2) + g(t),

where g(t) is our integration constant (y being the variable of integration, any function of t has derivative zero with respect to y and so is constant in this integral).

F_t = y cos(t y) + 1 implies that

F = integral( (y cos(t y) + 1) dt) = -sin(t y) + h(y),

where h(y) is constant with respect to t, the variable of integration.

If h(y) = e^(y^2) and g(t) = 0, our result is

F = -sin(t y) + e^(y^2) .

dF = 0 means that

F = c,

where c is constant, so

-sin(t y) + e^(y^2) = c.

The initial condition is that y(0) = pi, so we have

-sin(0) + e^(pi^2) = c

and c = e^(pi^2).

Our implicit solution is therefore given by the equation

-sin(t y) + e^(y^2) = e^(pi^2).

*@

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution: 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

*********************************************

Question:  3.3.10.  If N(y, t) * y ' + t^2 + y^2 sin(t) = 0 is exact, what is the most general possible form of N(y, t)?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution: 

N = M_y = 2y sin t

F_y = 2 y sin t --> F= y^2 sin t + h(t)

F_t = t^2 + y^2 sin t --> F = 1/3t^3 + y^2 sin t + g(y)

Thus generally:

N = 2y sin t

 

@& Good, but you can have a function g(y) as integration constant:

The equation is of the form

N(y, t) dy + (t^2 + y^2) sin(t) dt = 0

It is exact if N_t = M_y, where

M_y = 2 y sin(t).

N_t = M_y so that

N = integral(M_y dt) = integral ( 2 y sin(t) dt ) = -2 y cos(t) + g(y),

where g(y) is the most general integration constant for integration with respect to t.

*@

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution: 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

*********************************************

Question:  3.3.12.  If y = -t - sqrt( 4 - t^2 ) is the solution of the differential equation (y + a t) y '  + (a y + b t) = 0 with initial condition y(0) = y_0, what are the values of a, b and y_0?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution: 

F_y = y+ at --> F = 1/2y^2 + yat + g(t)

F_t = ay + bt --> F = aty + 1/2bt^2 + h(y)

g(t) = 1/bt^2

h(y) = 1/2y^2

1/2y^2 + aty + b/2t^2 = C

Here y should be able to solve for y to obtain the given solution but I can't seem to do that but I think the constants can be found anyway.

a= -1, b = 2, y_0 = -2

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

@& Check the following and see if you agree.

If y = -t - sqrt( 4 - t^2 ) is the solution of the differential equation (y + a t) y '  + (a y + b t) = 0 with initial condition y(0) = y_0, what are the values of a, b and y_0?

This equation is exact, with M = (y + a t) so that M_y = a, and N = (a y + b t) so that N_t = a.

Thus the equation is of the form dF = 0 with

F = integral( (y + at) dy) = y^2 / 2 + a t y + g(t)

and

F = integral( (a y + b t) dt) = a y t + b t^2 / 2 + h(y).

We reconcile the two forms of F by letting g(t) = b t^2 / 2 and h(y) = y^2 / 2, so that

F = y^2 / 2 + b t^2 / 2 + a t y.

dF = 0 has solution F = c, where c is constant, so the implicit solution is

y^2 / 2 + b t^2 / 2 + a t y = c.

If y = -t - sqrt( 4 - t^2 ) then y^2 = t^2 + (4 - t^2) + 2 t sqrt(4 - t^2) = 4 + 2 t sqr(4 - t^2). Substituting for y in the equation we therefore obtain

4 + 2 t sqr(4 - t^2) + b t^2 / 2 + a t ( -t - sqrt( 4 - t^2) ) = c

(2 t - a t) sqrt( 4 - t^2) + (b/2 - a) t^2 + 4 = c

Thus

2 t - a t = 0

b/2 - a = 0

c = 4

and it follows that

a = 2, b = 4

and when t = 0 we have

y_0^2 / 2 = 4

so that y_0 = 2 sqrt(2).

*@

.............................................

Given Solution: 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:"

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

________________________________________

#$&*